Factors that foster or prevent sense of belonging among social and health care managers. Issue 4 (1st October 2018) - Lampinen, Mai-Stiina; Konu, Anne Irmeli; Kettunen, Tarja; Suutala, Elina Annikki
Abstract : Purpose: The purpose of this study is to identify factors that foster or prevent sense of belonging among frontline and middle managers in social and health-care services in Finland. Design/methodology/approach: The data have been collected among social and health-care managers ( n = 135; 64 per cent nursing managers) through two open-ended questions in a questionnaire concerning sense of community. The results of the open-ended questions have been analyzed using qualitative content analysis. Findings: Among managers, six categories of factors that foster sense of belonging (open interaction, effective conversation culture, support and encouragement, common values, a shared vision of the work and its objectives and structure of leadership) and five categories of factors that prevent sense of belonging (negative work atmosphere, lack of common time, structural solutions in the organization, problems that occur in the organizational level and problems related to leadership and management) have been identified. Practical implications: The resulting information can be used to develop sense of belonging among managers at all levels of organization (horizontal and vertical). Originality/value: Paying attention to the quantity and quality of interaction and to structural solutions in the organization can affect the sense of belonging among frontline managers and middle managers.